The South Carolina Digital Watershed: End-to-End Support for Real-Time Management of Water Resources. (8th July 2010) - Eidson, G. W.; Esswein, S. T.; Gemmill, J. B.; Hallstrom, J. O.; Howard, T. R.; Lawrence, J. K.; Post, C. J.; Sawyer, C. B.; Wang, K.-C.; White, D. L.
Abstract : Water resources are under unprecedented strain. The combined effects of population growth, climate change, and rural industrialization have led to greater demand for an increasingly scarce resource. Ensuring that communities have adequate access to water—an essential requirement for community health and prosperity—requires finegrained management policies based on real-time in situ data, both environmental and hydrological. To address this requirement at the state level, we have developed the South Carolina Digital Watershed, an end-to-end system for monitoring water resources. In this paper, we describe the design and implementation of the core system components: (i) in situ sensing hardware, (ii) collection and uplink facilities, (iii) data streaming middleware, and (iv) back-end repository and presentation services. We conclude by discussing key organizational and technical challenges encountered during the development process.